Enhanced adsorption and reduction performance of nitrate by Fe–Pd–Fe3O4 embedded multi-walled carbon nanotubes - Wang, Zeyu; Dai, Luyao; Yao, Jiachao; Guo, Tianjiao; Hrynsphan, Dzmitry; Tatsiana, Savitskaya; Chen, Jun (Chemosphere (Oxford), 2021)
Multi walled carbon nanotubes (MWCNTs) have attracted more and more attention as adsorbents due to their excellent adsorption properties. By loading metal particles on MWCNTs, the chemical reduction ability of adsorbed pollutants could be provided, so as to achieve the purpose of adsorption and degradation of pollutants. Therefore, the removal process of NO3−-N by Fe–Pd–Fe3O4/MWCNTs was studied, including rapid adsorption of initial pollutants, gradual reduction of intermediate products and re-adsorption of final products. The results showed that Fe–Pd–Fe3O4/MWCNTs completely removed NO3−-N within 2 h, 39% and 25% of which were converted into NO2−-N and NH4+-N. The adsorption efficiency, kinetics, capacity and adsorption energy all followed the order of NH4+-N > NO2−-N > NO3−-N. With the recoverability and reusability of Fe–Pd–Fe3O4/MWCNTs having been confirmed in 5 consecutive cycles, the removal rate of NO3−-N still reached 43%. It has been shown that MWCNTs prolonged the reducing power for NO3−-N, due to avoiding the aggregation of metal particles. The rapid adsorption of initial pollutants, effective stepwise reduction and convenient recovery processes were of great value for the rehabilitation of polluted water. [Display omitted] •50 mg/L Fe–Pd–Fe3O4/MWCNTs completely removed 100 mg/L NO3−-N within 2 h.•36% of adsorbed NO3−-N was converted into N2 or N2O.•The removal efficiency of NO3−-N reached 43% by Fe–Pd–Fe3O4/MWCNTs in 5 cycles.